(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study conducts an empirical analysis of stock return drivers and volatility dynamics in the Indian equity market, focusing on select Nifty 50 companies. It comparatively examines the Fama-French 5-Factor model and GARCH models. The Fama-French 5-Factor model demonstrates limited explanatory power for the returns of large-cap stocks, indicating that company-specific strategies, industry trends, and macroeconomic conditions are more influential than traditional factors. This suggests that a simple factor-based approach may not fully capture the complexities of alpha generation in India. In contrast, the GARCH model consistently and effectively captures dynamic, time-varying volatility, as evidenced by pronounced spikes during periods of heightened risk, such as the COVID-19 pandemic in early 2020. This dynamic risk modelling approach offers a more realistic and actionable understanding of risk compared to static measures, proving crucial for robust portfolio management and informed investment decisions in the evolving Indian equity market.